EFL WRITTEN ONLINE DISCUSSION ABOUT VIRAL TOPICS ON PADLET DURING THE COVID-19 PANDEMIC - Angela Bayu Pertama Sari (PROJECT (Professional Journal of English Education), 2022)
Covid-19 pandemic has greatly affected the EFL learning system. With the support of advanced technology, students and educators now have a limitless concept of time and space for learning. One of the worthy web tools for learning is padlet. This research aims to project the students’ perception of what they liked and disliked from the online discussion conducted through padlet. The research participants were 130 non-English students from one of the private universities in Yogyakarta. This study used the qualitative descriptive method and employed thematic data analysis. The data collecting method used open-ended questionnaires. Based on the research findings, the positive things students liked from padlet online discussion on the viral topics are: (1) it improves their skills and knowledge, (2) it creates an enjoyable learning atmosphere, (3) serves practicality. The negative things that the students dislike from an padlet online discussion on viral topics are (1) internet connection issue, (2) shallow and monotonous discussion results, (3) creating the feeling of missing out. Keywords:  EFL, Online Discussion, Padlet, Viral, Covid-19